Results of Surgery for Low-Grade Brain Arteriovenous Malformation Resection by Early Career Neurosurgeons: An Observational Study. Issue 3 (28th March 2018) - Patel, Nirav J; Bervini, David; Eftekhar, Behzad; Davidson, Andrew Stewart; Walsh, Daniel C; Assaad, Nazih N; Morgan, Michael Kerin
Abstract: BACKGROUND: For sustainability of arteriovenous malformation (AVM) surgery, results from early career cerebrovascular neurosurgeons (ECCNs) must be acceptably safe. OBJECTIVE: To determine whether ECCNs performance of Spetzler–Ponce Class A AVM (SPC A) resection can be acceptably safe. METHODS: ECCNs completing a cerebrovascular fellowship (2004-2015) with the last author were included. Inclusion of the ECCN cases occurred if they: had a prospective database of all AVM cases since commencing independent practice; were the primary surgeon on SPC A; and had made the significant management decisions. All SPC A surgical cases from the beginning of the ECCN's independent surgical practice to a maximum of 8 yr were included. An adverse outcome was considered a complication of surgery leading to a new permanent neurological deficit with a last modified Rankin Scale score >1. A cumulative summation (Cusum) plot examined the performance of each surgery. The highest acceptable level of adverse outcomes for the Cusum was 3.3%, derived from the upper 95% confidence interval of the last author's reported series. RESULTS: Six ECCNs contributed 110 cases for analysis. The median number of SPC A cases operated by each ECCN was 16.5 (range 4-40). Preoperative embolization was performed in 5 (4.5%). The incidence of adverse outcomes was 1.8% (95% confidence interval: <0.01%-6.8%). At no point during the accumulated series did the combined cohort become unacceptable by the Cusum plot. CONCLUSION: ECCNs with appropriate training appointed to large-volume cerebrovascular centers can achieve results for surgery for SPC A that are not appreciably worse than those published from high-volume neurosurgeons.